RANCANGAN SISTEM INFORMASI MANAJEMEN SEDIAAN PADA PT. OASINDO RAYA - Budi Hermawan; Fitri Novika Widjaja; Stefanus Budy Widjaja S. (CALYPTRA, 2018)
The design of this dosage management information system has the purpose to support PT. Oasindo Raya in making the decision on the process of buying and selling to be more effective and efficient, The drafting is necessary because PT. Oasindo Raya still uses the conventional way of managing its business especially in the recording process so that it becomes less effective and efficient regarding the process of buying and selling its products. A stock management information system is needed to develop the company better in its operational processes. With the design is expected to produce the information needed for decision making quickly and appropriately in order to develop the business of PT. Oasindo Raya in the future. This design applies System Development Life Cycle with 8 stages and uses the addition of Electronic Data Proccessing (EDP) that is with Software Inventory that requires hardware, software, users and database used to run well as expected. The draft regulates the recording of the process of purchasing, selling, inventory stock at the beginning and ending and all the processes related to the stock of both out and coming in PT. Oasindo Raya. The design of this management information system shows that the addition of EDP can improve the operational process of PT. Oasindo Raya is more effective and efficient because all the necessary information can be known quickly and accurately.